On the solution of generalized time-fractional telegraphic equation. Issue 1 (31st December 2023) - Albalawi, Kholoud Saad; Shokhanda, Rachana; Goswami, Pranay
Abstract : In this article, we have introduced a nonlinear extension of the generalized time-fractional telegraph equation (TFTE). Further, an analytical solution to this equation has been obtained by using the Laplace homotopy perturbation method (LHPM). Some known results are also discussed as special cases which supports the strength and viability of the work.